Value-based payment models in primary care: An assessment of the Menzis Shared Savings programme in the Netherlands - Lindner, Luca (OECD Publishing, 2023)
The Menzis Shared Savings Program was initiated in 2014 by the Dutch insurer Menzis and the national primary care organisation Arts en Zorg, and is among the first value-based payment models for primary care in Europe. It runs as a complement to the current - volume-driven - primary care payment system. This paper reviews the evidence of the impact of this programme against its stated objectives. The Menzis Shared Savings Program led to a lower volume of care, particularly in terms of referrals to specialist care, laboratory care and general practitioners care. Main facilitating factors were the advanced data infrastructure in place, communication and transparency about the programme's parameters, and the programme's focus on mitigating financial risk and uncertainty for providers. Shared savings models - even when added as a mere complement to existing volume-driven payment methods - could enhance value in health systems
Keywords: Social Issues/Migration/Health